Durability of Alkali Activated Blast Furnace Slag. Issue 1 (October 2015) - Ellis, K; Alharbi, N; Matheu, P S; Varela, B; Hailstone, R
Abstract: The alkali activation of blast furnace slag has the potential to reduce the environmental impact of cementitious materials and to be applied in geographic zones where weather is a factor that negatively affects performance of materials based on Ordinary Portland Cement. The scientific literature provides many examples of alkali activated slag with high compressive strengths; however research into the durability and resistance to aggressive environments is still necessary for applications in harsh weather conditions. In this study two design mixes of blast furnace slag with mine tailings were activated with a potassium based solution. The design mixes were characterized by scanning electron microscopy, BET analysis and compressive strength testing. Freeze-thaw testing up to 100 freeze-thaw cycles was performed in 10% road salt solution. Our findings included compressive strength of up to 100 MPa after 28 days of curing and 120 MPa after freeze-thaw testing. The relationship between pore size, compressive strength, and compressive strength after freeze-thaw was explored.